Manajemen Pelaksanaan Program Siger Sultan dalam Pelayanan Administrasi Kependudukan bagi Penyandang Disabilitas pada Dinas Kependudukan dan Pencatatan Sipil Kota Bandar Lampung - Anisa Zulfa Nabila; Dedy Hermawan (Administrativa : Jurnal Birokrasi, Kebijakan dan Pelayanan Publik, 2026)
The Siger Sultan Program is an innovative population administration service aimed at increasing population identity ownership, specifically e-KTP (electronic ID card), for vulnerable groups such as people with disabilities. This study aims to analyze the implementation management of the Siger Sultan Program in increasing population identity ownership for people with disabilities in Bandar Lampung City. The research method used is a qualitative approach with a descriptive research type. Data were obtained through literature review and document analysis. The research results indicate that program implementation adheres to management functions, including planning, organizing, implementing, and controlling. However, implementation still faces challenges, including limited human resources, inadequate program outreach, and accessibility barriers for people with disabilities. Therefore, strengthening coordination, increasing resources, and adopting an inclusive service approach is necessary for the program to run optimally.